Improvement in antimicrobial properties of titanium by diethyl phosphite plasma-based surface modification. (December 2020) - Kaleli-Can, Gizem; Özgüzar, Hatice Ferda; Kahriman, Selahattin; Türkal, Miranda; Göçmen, Jülide Sedef; Yurtçu, Erkan; Mutlu, Mehmet
Graphical abstract: Abstract: Titanium (Ti) has been commonly used as a biomaterial for dental applications. However, they have struggled with the formation of polymicrobial infections leading to peri-implantitis. In this research, antimicrobial activity of titanium modified via diethyl phosphite (DEP) plasma onto Staphylococcus aureus ( S. aureus ) and Candida albicans ( C. albicans ), the two most frequently encountered pathogens in peri-implantitis, were investigated. Surface modification with DEP was achieved with plasma polymerization technique in a low-pressure/radio-frequency plasma using 75 W of plasma power and 10 min of exposure time under 0.15 mbar. Hydrophilicity, surface energy and roughness of Ti surface was increased and anionic Ti surface became amphoteric after surface modification according to physical and chemical examinations. This process significantly enhanced the antimicrobial efficiency of Ti towards S. aureus and C. albicans cells compared to control groups via contact killing. Moreover, DEP coating shown excellent compatibility with 93 % of L929 fibroblast cell viability. These findings revealed that amphoteric plasma polymer prepared from DEP offers promising solution for preventing biofilm formation on Ti.